(untitled) (Web of Teachers: Inderscience Research, 2026)
The article reflects on the role of Abdurakhman Jami in the upbringing of the perfect generation and its importance today, based on the researches of Orientalist Y.E.Bertels. Along with this, Jami’s religious-mystical and educational views, their place and importance in social life are revealed. The thinker’s anger, lust, and power of speech combine to create justice.